Estimasi Magnitudo Paleoearthquake Dengan Metode Magnitude Bound - Desi Kiswiranti (Department of Physics Universitas Gadjah Mada, 2018)
Yogyakarta was recorded unique seismic on the temple buildings such as Kedulan, Plaosan, Gampingan, Morangan and Kadisoka deformed on the body of the building due to liquefaction. Liquefaction structure found on the site of sand pillar, sand fissure and sand sill consisting of sand material that intrution other sediment layer. Magnitude Bound method is used to estimate the paleoearthquake magnitudes from paleoliquefaction data by utilizing the farthest distance liquefaction formed with epicenter earthquake. The application of the method shows that Yogyakarta had a large earthquake with magnitude of 6.25-6.5 M. The earthquake can cause severe physical damage, and can lead to secondary disasters such as liquefaction.